2021
DOI: 10.1155/2021/4654302
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Ferroptosis-Related Signature Associated with Prognosis and Immune Infiltration in Adrenocortical Carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare malignant tumor with poor prognosis. Ferroptosis, a new form of cell death, differs from other forms of cell death and plays a vital role in tumor progress. Our study aimed to establish a ferroptosis-related signature with prognostic value in ACC. RNA-seq data and corresponding clinical characteristics for ACC were downloaded from TCGA and GEO databases. Genes included in ferroptosis risk signature were assessed by univariable and multivariable Cox regression analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…However, clinical data show that only less than 10% of patients with GBM response to immunotherapy because of the low immunogenicity of GBM [ 10 , 48 ]. It has been shown that ferroptosis of cancer cells release high-mobility group box 1 (HMGB1) in an autophagy dependent manner [ 49 ], which increases the immunogenicity of cancer cells and promotes the maturation of DC cells [ 50 52 ]. The matured DC cells presents antigen to T lymphocytes and activates innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical data show that only less than 10% of patients with GBM response to immunotherapy because of the low immunogenicity of GBM [ 10 , 48 ]. It has been shown that ferroptosis of cancer cells release high-mobility group box 1 (HMGB1) in an autophagy dependent manner [ 49 ], which increases the immunogenicity of cancer cells and promotes the maturation of DC cells [ 50 52 ]. The matured DC cells presents antigen to T lymphocytes and activates innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that PCBP2 binding to severely oxidized RNA inhibited apoptosis induced by oxidative stress ( 78 ). Moreover, PCBP2 is one of the ferroptosis risk signature genes and can predict the prognosis of adrenocortical carcinoma in combination with the other five ferroptosis risk signature genes ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that an FRG-based prognostic nomogram could improve the estimation of the survival rate of patients with clear cell renal cell carcinoma ( 50 ). Similarly, a novel ferroptosis risk signature could be useful in predicting prognosis and reflecting immune infiltration in adrenocortical carcinoma ( 51 ). These analyses also suggested that the FS might be a potential and reliable prognostic biomarker in CC.…”
Section: Discussionmentioning
confidence: 99%